Neurobehavioral Consequences of Chronic Lead Intoxication: Effects of Vitamin E Supplementation - Ibironke, G.F.; Adu, S.T. (Нейрофизиология, 2015)
We investigated the effects of vitamin E supplementation on neurobehavioral alterations induced
by chronic ingestion of lead acetate in mice. The animals were divided into three main groups,
group 1 (control) given with normal saline (10 ml/kg) and groups 2 and 3 given with 3000 mg/kg
lead acetate alone and in combination with 13 IU of vitamin E, respectively, for a period of
90 days. Lead intoxication resulted in significant (P < 0.05) reduction of the number of head dips
in the hole-board test and the time spent in the open arm of the elevated plus maze test, compared
with the control. Intoxication also induced increased pain sensitivity, as shown by significant
(P < 0.05) reduction in the tail flick latency and increase in the frequency of abdominal
constrictions in the writhing test. The periods of immobility in both tail suspension and
forced swimming tests in intoxicated animals were greater, as compared with the control.
Co-administration of vitamin E with lead in group 3 significantly (P < 0.05) reversed all the
mentioned shifts (increased the number of head dips and time spent in the maze open arm,
increased the tail flick latency, decreased the frequency of writhings, and decreased the periods
of immobility in the forced swimming and tail suspension tests). Thus, vitamin E treatment
is capable of effectively attenuating the negative neurobehavioral consequences of lead
intoxication. Ми досліджували зміни нейроповедінкових показників у
мишей, викликані хронічним пероральним уведенням ацетату свинцю, та корекцію цих змін за допомогою вітаміну
Е. Тварини були поділені на три групи: контрольну групу 1,
що отримувала фізіологічний розчин (10 мл/кг), та групи
2 і 3, котрим протягом 90 діб уводили 3000 мг/кг ацетату
свинцю ізольовано або в комбінації з 13 М.О. вітаміну Е
відповідно. Свинцева інтоксикація зумовлювала істотне
(P < 0.05) зменшення кількості зазирань в отвори під час
проходження тесту «отвори в дошці» та часу, проведеного
у відкритих рукавах «підвищеного» лабіринту. Інтоксикація також призводила до підвищення чутливості до болю,
про що свідчили істотні скорочення латентного періоду відсмикування хвоста та збільшення кількості «корчів», індукованих уведенням оцтової кислоти, у відповідних тестах.
Періоди нерухомості у тестах підвішування за хвіст та примусового плавання в інтоксикованих тварин були довшими, ніж у контролі. Паралельне уведення вітаміну Е тваринам групи 3 істотно (P < 0.05) нейтралізувало вказані
негативні зрушення. Ставали більшими число зазирань в
отвори та час, проведений у відкритих рукавах лабіринту;
латентний період відсмикування хвоста подовжувався, а
число «корчів» зменшувалося; періоди імобілізації у згаданих вище тестах скорочувалися. Отже, вітамін Е, будучи
потужним антиоксидантом, ефективно згладжує негативні
нейроповедінкові наслідки свинцевої інтоксикації.